(untitled) (Nepalese Medical Journal, 2018)
The toxicity of Baclofen is extremely unusual. However, its predominant renal clearance makes its vulnerable in patients with impaired renal function. Clinical manifestations may begin as early as 2-3 days after starting the drug, even with a smaller dosage. A 73-year-old man with end-stage renal disease on maintenance hemodialysis was admitted to our emergency department with progressive confusion, hallucination and a generalized decrease in muscular tone. There was no significant metabolic or infectious etiology that could have clarified his condition. A thorough laboratory and imaging workup was negative too. A detailed history of his medication revealed that he had recently been prescribed baclofen for neck muscular spasm (10mg twice daily). He was then diagnosed with baclofen toxicity and was treated with intensive hemodialysis. During his admission, few sessions of hemodialysis on consecutive days, eventually produced expected clinical improvement and a complete return to his previous baseline mental status. Nepalese Medical Journal, vol.1, No. 1, 2018, page: 54-56